Kinase and Phosphatase Engagement Is Dissociated Between Memory Formation and Extinction - Pagani, Mario Rafael; Merlo, Emiliano (Frontiers in Molecular Neuroscience, 2019)
Associative long-term memories (LTMs) support long-lasting behavioural changes resulting from sensory experiences. Retrieval of a stable LTM by means of a large number of conditioned stimulus (CS) alone presentations produces inhibition of the original memory through extinction. Currently, there are two opposing hypotheses to account for the neural mechanisms supporting extinction. The unlearning hypothesis posits that extinction affects the original memory trace by reverting the synaptic changes supporting LTM. On the contrary, the new learning hypothesis proposes that extinction is simply the formation of a new associative memory that inhibits the expression of the original one. We propose that detailed analysis of extinction-associated molecular mechanisms could help distinguish between these hypotheses. Here we will review experimental evidence regarding the role of protein kinases and phosphatases on LTM formation and extinction. Even though kinases and phosphatases regulate both memory processes, their participation appears to be dissociated. LTM formation recruits kinases, but is constrained by phosphatases. Memory extinction presents a more diverse molecular landscape, requiring phosphatases and some kinases, but also being constrained by kinase activity. Based on the available evidence, we propose a new theoretical model for memory extinction: a neuronal segregation of kinases and phosphatases supports a combination of time-dependent reversible inhibition of the original memory (CS-US), with establishment of a new associative memory trace (CS-noUS).